The toying boy, the speaking body toy: cartoon, communication and imagination in child development - Pereira, Isac dos Santos; Peruzzo, Cicilia Maria Krohling (Comunicação & Educação, 2020)
From theoretical construct based on the construction of language and the imaginary seen by the field of neurosciences and philosophy, along with the productions of cartoons, the text discusses the benefits of audiovisual productions aimed at children applied to teaching and learning. It is an approach based on bibliographic research and aims to critically reflect on audiovisual media as subsidiary objects in the development of language and knowledge of the child, within the educational framework. It also aims to discuss the relations between communication and education.